ICTUS Journal is Born (Ictus, 2020)
The editorial letter of Welcome to ICTUS the Journal of Cerebral Vascular Disease, published by the members of the Editorial Board of the Ictus Journal is presented.
Keywords: stroke; cerebrovascular diseases; amevasc